Knee and hip joint dynamics differ between sprinting and Nordic hamstring exercises - Steudel, K.; Haralabidis, N.; Gurchiek, R.; Hicks, J.; Delp, S. (Journal of Biomechanics, 2026)
Sprinting and the Nordic hamstring exercise (NHE) are common training modalities used to reduce hamstring injury risk, but the differences in the biomechanical demands of sprinting and the NHE are unclear. We conducted an exploratory analysis comparing knee and hip joint kinematics and kinetics, and biceps femoris long head (BFLH) muscle-tendon unit length and velocity during the flight phase of sprinting and the NHE. We collected motion capture and force data from fourteen athletic participants (8 males, 6 females) running (4-8 m/s) and performing the NHE. We used this experimental data and musculoskeletal modeling to compute joint kinematics and kinetics and estimate the BFLH muscle-tendon unit length and velocity for all running speeds and the NHE. Sprinting, for all speeds, puts the BFLH at longer lengths (p < 0.001) and higher lengthening velocities (p < 0.001) than the NHE. The NHE requires participants to generate peak knee flexion moments that are smaller than for running at 6 m/s and above (p < 0.001), and peak negative knee flexion powers that are less than 5% of all running speeds (p < 0.001). However, the duration of each NHE repetition is approximately 60 times longer than the BFLH lengthening portion of the flight phase of running, resulting in greater negative knee work for running at 6 m/s and below (p < 0.001) but less at 7.5 m/s and above (p < 0.001). The results of this study provide necessary quantitative information to compare the biomechanical demands of sprinting and the NHE.